2007
DOI: 10.1159/000099052
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Substrates for First-Branch Pulmonary Arterial Hypoplasia in Transposition of the Great Arteries

Abstract: Background: Distal right-sided outflow obstruction remains a problem after arterial switch operation. We studied the anatomical features of the pulmonary trunk (PT) and its branches that are susceptible to right and left pulmonary arterial (RPA and LPA) hypoplasia in transposition of the great arteries (TGA). Methods: One hundred and one angiograms of TGA performed between 1981 and 1996 were viewed, and Polaroid photos were taken at end-systole. The diameters of RPA, LPA, PT, duct, ascending aorta, and angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…On the other hand, while the conventional measurements in our study were consistent with reported literature, 8,25 they only take into account PA stenosis and do not correlate with RV afterload. Our novel measurements (R c , R c-w , and bending angle) quantify a phenomenon previously observed via angiography and described by Chen et al 26 and Chiu et al 27 as "narrowing of the pulmonary arch window." The abnormal curvatures and bending angles in the branch pulmonary arteries are likely an effect from multiple geometrical components, particularly enlargement of prox-AscAo and a rightward MPA position.…”
Section: Commentsupporting
confidence: 53%
See 1 more Smart Citation
“…On the other hand, while the conventional measurements in our study were consistent with reported literature, 8,25 they only take into account PA stenosis and do not correlate with RV afterload. Our novel measurements (R c , R c-w , and bending angle) quantify a phenomenon previously observed via angiography and described by Chen et al 26 and Chiu et al 27 as "narrowing of the pulmonary arch window." The abnormal curvatures and bending angles in the branch pulmonary arteries are likely an effect from multiple geometrical components, particularly enlargement of prox-AscAo and a rightward MPA position.…”
Section: Commentsupporting
confidence: 53%
“…As shown in Table 4, conventional measurements of PA size (Nakata index, RPA/total area ratio) correlated with differential pulmonary blood flow (r ¼ 0.49, P ¼ .0011) and did not correlate with RV afterload (r ¼ À0. 26…”
Section: Correlations With Rv Afterload Differential Pulmonary Bloodmentioning
confidence: 99%
“…Central PA hypoplasia, which is frequently seen in TGA, is related to posterior inclination of the proximal MPA in this setting. 28 We have also showed that the same pathogenesis would lead to smaller PA size after a Senning operation than ASO with Lecompte maneuver. In addition, Lecompte with Pacifico’s modification (direct connection between the distal MPA and the aortic sinus defect), which mobilized the proximal MPA toward the anterior aspect farther than did the patch repair of the sinus defect, could facilitate better PA growth after ASO.…”
Section: Anatomical Featuresmentioning
confidence: 54%
“…Its pathogenesis was related to a posterior inclination of the proximal MPA in this setting (Fig. 1A) [8]. To facilitate PA growth, it is best to mobilise the posterior inclination of the proximal MPA and restore its 'normal' position ( Fig.…”
Section: Widening Of Main To Branch Pa Anglementioning
confidence: 92%